Comparison of thiocyanate and selenocyanate for potentiation of antimicrobial photodynamic therapy: Potentiation of aPDT with KSCN and KSeCN - Huang, Liyi (J Biophotonics, 2018)
We have previously shown that antimicrobial photodynamic therapy (aPDT) mediated by different photosensitizers can be potentiated by a variety of inorganic salts. Potassium thiocyanate potentiated aPDT mediated by methylene blue (MB), while potassium selenocyanate potentiated aPDT mediated by MB, Rose Bengal and the anionic porphyrin TPPS4. However, the mechanisms of action that were proposed were fundamentally different. In the present study we compare these two salts (KSCN and KSeCN) with different light-activated photosensitizers (PS) and different oxidative reactions for killing Gram-positive and Gram-negative bacteria. Overall KSeCN was more powerful than KSCN, and worked with a wider range of PS, while KSCN only worked with phenothiazinium salts. KSeCN produced killing when cells were added after light suggesting production of a semi-stable species called selenocyanogen, (SeCN)(2). We tested three different oxidative reactions that can all potentially kill bacteria: lead tetraacetate; Fenton reagent (hydrogen peroxide and ferrous sulfate); hydrogen peroxide and horseradish peroxidase (H(2)O(2)/HRP). In every case KSeCN was substantially more effective (several logs) than KSCN in potentiating the bacterial killing. We conclude that (SeCN)(2) is the mediator for aPDT using KSeCN, while sulfur trioxide radical anion is the mediator for KSCN using phenothiaziums. For H(2)O(2)/HRP with KSCN, hypothiocyanite (OSCN-) is proposed to be the antibacterial agent in the literature, while hyposelenocyanite is said not to exist. Lead tetracetate is known to produce (SeCN)(2) from KSeCN as well as the analogous (SCN)(2) from KSCN. The mediators from Fenton reaction are unclear (pseudohalogen radical ions?) Both KSCN (which occurs naturally in the human body) and KSeCN may be clinically applicable.